DEGRADAÇÃO FOTOQUÍMICA DE CLORIDRATO DE CIPROFLOXACINO USANDO FILMES DE TiO2NT E Ag-TiO2NT - SCHELEDER, MICHELLE ZANELLA (2021)
With the water crisis that the world has been facing in the last decade, there has been a great appeal to the use of so-called reuse water from effluents. However, not all effluents can be reused immediately after secondary treatment as they may contain pathogenic microorganisms and/or drugs that promote the emergence of resistant bacteria, which can generate a public health crisis. In Brazil, currently, there is a lack of efficient methods for the decontamination and disinfection of this type of effluent, therefore, the present work has as its main scientific and technological contribution, the development of technologies that make possible the chemical decontamination of effluents. The study of effluent decontamination was carried out through the degradation of the drug ciprofloxacin hydrochloride via photochemical processes using electrochemically synthesized titanium dioxide (TiO2) nanotubes. Effluent decontamination was studied using two different methodologies, heterogeneous photocatalysis, and photoelectrocatalysis. In both processes, electrochemically synthesized TiO2 nanotube (TiO2NT) films were used through the application of 3 different values of potential (20, 30, and 40 V) to synthesize films with high surface area and high photocatalytic activity. To optimize the photocatalytic properties of the synthesized films, they were subjected to photochemical sensitization with silver, which aims to reduce the bandgap value of these materials by shifting the light absorption to the visible region, which is an extremely desirable characteristic for the use of photocatalysts for the treatment of effluents, since this characteristic makes it possible to use sunlight. All films were subjected to a heat treatment to convert the amorphous oxide to the anatase crystalline phase, which is responsible for the photocatalytic activity of this material. The synthesized films were also characterized in terms of their morphology and microstructure to identify structural properties responsible for the increase in photocatalytic activity. An ecotoxicity study was carried out using three biomarkers and the results show that although the degradation of ciprofloxacin hydrochloride occurs faster when using the photoelectrocatalysis technique, the generated effluent is more toxic. Through these studies, it was observed that for the films decorated with silver there is no increase in photoactivity. In the ecotoxicity tests, the effluents generated from the silver films showed greater toxicity. Therefore, the applied technique with the best performance in drug degradation was photoelectrocatalysis using pure films.